2022
DOI: 10.1002/jor.25463
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐rich plasma versus corticosteroid injections in the management of patients with rotator cuff disease: A systematic review and meta‐analysis

Abstract: Platelet-rich plasma (PRP) is an alternative to corticosteroid (CS) injections in managing rotator cuff disease. This meta-analysis investigated differences between PRP and CS for function and pain scores in significance and minimal clinical important difference (MCID). A literature search of Ovid Cochrane Library, Medline, Embase, Epub, and Scopus was conducted from inception to October 28, 2021.Eligible studies reported patients older than 18 years with a diagnosis of rotator cuff disease. This review was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The proliferation of studies investigating the use of PRPi for chronic tendinopathies in recent years has been analyzed and commented on repeatedly in the literature; 8,26,27 similarly, the lack of consensus and certainty as to its clinical effectiveness has been highlighted� 28 Factors contributing to this uncertainty have been outlined in the relevant literature, and are similar to those identified in this report (e.g., small RCTs of limited quality with no or small effect sizes, 2 as well as considerable lack of clarity and/or variability in PRPi components and treatment protocols), 6,27,[29][30][31] which have been identified as challenges in drawing conclusions from the research investigating PRPi's effectiveness� One of the included overviews summarized in this report made particular mention of the need for larger and more methodologically rigorous RCTs in the future, given the limited quality of existing primary research and the consequent lack of consensus across multiple evidence syntheses on the topic� 18 Another pointed out that demonstrating the clinical effectiveness of PRPi as compared to placebo is a necessary precursor to investigation of its effectiveness against other interventions; that is, if PRPi is demonstrated to be effective against placebo, then its effectiveness against other interventions may be of interest, whereas if PRPi is demonstrated to have no comparative effect versus placebo, then further investigation of its effectiveness is not warranted� 23,32 CADTH has conducted past reviews of the clinical evidence describing PRPi for other indications, including orthopedic conditions, trauma, 33 and low back pain� 34 While the conditions reviewed in those reports are not entirely relevant to the research question posed in this report, it is notable that both reports similarly identified a lack of conclusive evidence supporting the clinical effectiveness of PRPi, with both indicating some evidence to support its safety, but a lack of evidence to support efficacy. 33,34 Despite the variability of the findings in the literature summarized in this review, there may yet be potential for the clinical effectiveness of PRPi, given that some of the findings summarized herein have demonstrated effectiveness; for instance, it may be that some formulations of PRPi are more effective than others, or that any effect of PRPi is observed at a longer (as opposed to shorter) duration of follow-up� It may also be that advances in the technology of platelet-rich therapies, such as platelet-rich fibrin 35 and plasma gel, 36 could hold promise for clearer or more consistent improvement in clinical outcomes among musculoskeletal conditions� Nonetheless, measurement of effectiveness that can support clinical and other decisions concerning the use of PRPi in chronic tendinopathies is necessarily supported by high-quality RCTs that use robust methods with sufficient sample sizes and standardized treatment protocols, and these remain a current limitation of the literature on this topic� 6 The inconclusive state o...…”
Section: Conclusion and Implications For Decision-or Policy-makingmentioning
confidence: 59%
“…The proliferation of studies investigating the use of PRPi for chronic tendinopathies in recent years has been analyzed and commented on repeatedly in the literature; 8,26,27 similarly, the lack of consensus and certainty as to its clinical effectiveness has been highlighted� 28 Factors contributing to this uncertainty have been outlined in the relevant literature, and are similar to those identified in this report (e.g., small RCTs of limited quality with no or small effect sizes, 2 as well as considerable lack of clarity and/or variability in PRPi components and treatment protocols), 6,27,[29][30][31] which have been identified as challenges in drawing conclusions from the research investigating PRPi's effectiveness� One of the included overviews summarized in this report made particular mention of the need for larger and more methodologically rigorous RCTs in the future, given the limited quality of existing primary research and the consequent lack of consensus across multiple evidence syntheses on the topic� 18 Another pointed out that demonstrating the clinical effectiveness of PRPi as compared to placebo is a necessary precursor to investigation of its effectiveness against other interventions; that is, if PRPi is demonstrated to be effective against placebo, then its effectiveness against other interventions may be of interest, whereas if PRPi is demonstrated to have no comparative effect versus placebo, then further investigation of its effectiveness is not warranted� 23,32 CADTH has conducted past reviews of the clinical evidence describing PRPi for other indications, including orthopedic conditions, trauma, 33 and low back pain� 34 While the conditions reviewed in those reports are not entirely relevant to the research question posed in this report, it is notable that both reports similarly identified a lack of conclusive evidence supporting the clinical effectiveness of PRPi, with both indicating some evidence to support its safety, but a lack of evidence to support efficacy. 33,34 Despite the variability of the findings in the literature summarized in this review, there may yet be potential for the clinical effectiveness of PRPi, given that some of the findings summarized herein have demonstrated effectiveness; for instance, it may be that some formulations of PRPi are more effective than others, or that any effect of PRPi is observed at a longer (as opposed to shorter) duration of follow-up� It may also be that advances in the technology of platelet-rich therapies, such as platelet-rich fibrin 35 and plasma gel, 36 could hold promise for clearer or more consistent improvement in clinical outcomes among musculoskeletal conditions� Nonetheless, measurement of effectiveness that can support clinical and other decisions concerning the use of PRPi in chronic tendinopathies is necessarily supported by high-quality RCTs that use robust methods with sufficient sample sizes and standardized treatment protocols, and these remain a current limitation of the literature on this topic� 6 The inconclusive state o...…”
Section: Conclusion and Implications For Decision-or Policy-makingmentioning
confidence: 59%